Ethnoarchaeological Survey of Obimo: A Fieldwork Report - Nwankwo, Elochukwu (Review of Knowledge Economy, 2014)
Iron smelting has been discovered to be amongst earliest technologies of Africans. It provided the earliest source of raw materials for blacksmithing in the African continent and at the same time formed a major part of the earliest economic base of the people. In the past many archaeological studies have concentrated on unearthing the earliest origin of this technology in the continent of Africa and its diversification or diffusion to other parts of the continent. Many of such studies have taken place in the Nsukka area of Enugu, Nigeria. Some of the communities in the Nsukka culture area have traces of this earliest technology in their environment with little or no significant answer to their origin. To this regard, this study is aimed at; studying one of the earliest technologies of Africans in this part of Nigeria, conduct a reconnaissance and ethnographic studies in Obimo community, excavate an iron smelting site in the community, determine the origin of the people and that of the iron smelting, and determine the cultural correlate of the extinct and extant societies of Obimo. Relevant research methods were adopted for efficient study of this kind. They include; reconnaissance survey, ethnography, excavation and documentary sources.